The Relationship of Physhical Activity, Sleep Duration, Breakfast and Fast Food Consumption Habits with The Prevalence of Overweight Among Elementary School Children - Mayangsari, Anggraeni Rizky; Wahyuningtyas, Widayani; Puspita, Ikha Deviyanti (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2018)
This study aims to determine the relation between physical activity, sleep duration, breakfast habits and fast food consumption habits at school-age chidren. This is a quantitative study using cross sectional design. The study was conducted in SDS Kartika VIII-5 Jakarta, as many as 102 fourth and fifth grade students were involved. The sampling technique used for this study was stratified sampling technique. The data collection instrument used questionnaire and interview. The data obtained were then analyzed by Chi-Square statistical test. The results showed that 63,7% of children were overweight. Bivariate result using Chi-Square statistical test showed that a significant relationship between physical activity (p = 0,003), sleep duration (p = 0,046), fast food habits (p = 0,035). There was a significant relation between physical activity, sleep duration, and fast food consumption habits with the prevalence of overweight.